2013
DOI: 10.1103/physreva.88.042713
|View full text |Cite
|
Sign up to set email alerts
|

Angular distributions for the electron-impact single ionization of sodium and magnesium

Abstract: We present angular distributions for the electron-impact single ionization of sodium and magnesium at intermediate incident electron energies. The results are obtained from a full-dimensionality solution of the two-active-electron time-dependent Schrödinger equation using the time-dependent close-coupling method. We compare calculated angular distributions with existing measurements. We find good overall agreement with measurements over a range of incident electron energies in both cases. We also calculate ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The TDCC calculations presented here have been discussed in detail previously [14]. The TDCC method centers around the propagation of a two-electron wavefunction that accounts for the interaction between the incoming electron and the ionized electron of the target.…”
Section: Iia Tdccmentioning
confidence: 99%
“…The TDCC calculations presented here have been discussed in detail previously [14]. The TDCC method centers around the propagation of a two-electron wavefunction that accounts for the interaction between the incoming electron and the ionized electron of the target.…”
Section: Iia Tdccmentioning
confidence: 99%
“…Our two-electron TDCC calculations used a radial mesh of (960) 2 points with variable mesh spacing of between 0.01 and 0.2 a.u. [24]. We found that it was necessary to include partial wave contributions from L = 0 − 14 to completely converge our calculations.…”
Section: Theorymentioning
confidence: 97%
“…(5) corrects a typographical error in the denominator of Eq. (9) of [24]. The function P LS l 1 l 2 (k 1 , k 2 , T ) is formed by projecting the final two-electron radial wavefunction (after propagation to a sufficiently long time T ) P LS l 1 l 2 (r 1 , r 2 , t = T ) onto the one-electron continuum orbitals.…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations